Land Use Evaluation on Entikong Border Area - Irsan, Robby (Universitas Pendidikan Indonesia, 2018)
Research on land use is very important, because land use has an influence on the physical environment as well as on the rules governing spatial planning. Various phenomenon of land use change happened from time to time. Changes in land use that occur in line with increased the number of people who directly impact on the need for increasing land. Entikong Sub district in Sanggau District is one of the areas directly adjacent to the state of Malaysia or Sarawak and is the first and the oldest cross-border entrance in Indonesia. Land use must be adjusted to the carrying capacity, because the land has limitations. Limitations can be seen from the ability of land, among others, land slope, soil type, rainfall, and lithology. The existence of land use interest is more dominant than carrying capacity, there can be land use that exceeds its ability. So the impact that occurred in the form of land and environmental degradation. The purpose of this study is to identify the type of land use and the carrying capacity of the Entikong border area to the land use change that occurred. The method of analysis used overlay method of land use map from two thousand eleven to two thousand seventeen, while the method of weighting or scoring to analyze the data by making a value to the existing circumstances. The results showed that the massive increased area from the mixed use yearsÂ of two thousand seventeen plantation land increased by sixty point six percent of the Entikong area and degreased the primary forest variables by only eighteen point six percent of the Entikong area by years of two thousand seventeen. This is indicates that the protected forests are experiencing degaradation of land use change towards mixed gardens where in this mixed plantation there are oil palm, rubber and pepper. While the results of research related to the carrying capacity of Entikong border area where the analysis of soil type with Score one which means having very bad interpretation of land carrying capacity, rainfall analysis with Score four means having good interpretation of land carrying capacity, analysis of the scores with score four which means supporting the carrying capacity of the land, while lithology analysis with Score three where the interpretation is on the carrying capacity of the land. The average total of interpretation scoring of land carrying capacity indicates number sixty, which means Entikong border area has a moderate land carrying capacity which can be recommended for the development of integrated area but must be attention to several issues related by land physical factors and environmental sustainability in order to be sustainable.